GE_GERICHTE P/8234/2016 vom 26. März 2018 - GE Cour de justice (2018)
INCENDIE INTENTIONNEL ; VIOLENCE CONTRE LES AUTORITÉS ; RESPONSABILITÉ RESTREINTE(DROIT PÉNAL) ; MESURE THÉRAPEUTIQUE INSTITUTIONNELLE | CP.221.al1; CP.221.al3; CP.285; CP.19.al2; CP.59.al1; CP.59.al3